Rancang Bangun Alat Pemotong Pantiaw - Yuliyanto Yuliyanto; Erwanto Erwanto; Gandis Sarahwikan Heyka; Novan Febrian; Syafira Qintasia (Manutech : Jurnal Teknologi Manufaktur, 2018)
Pantiaw is one of the traditional dish made from rice flour served with fish meat grinder and other ingredients. The design of this pantiaw cutting tool uses a press system using a lever. Based on the survey that has been done at the residence of mrs. Yuli, pantiaw produce 8 kg daily. The obstacle faced by yulimother at this time is the process of cutting pantiaw still using scissors or knives sliced one by one. So that takes longer time is 45 minutes to 1 hour. The purpose of making this pantiaw cutting tool is to cut the pantiaw uniformly in a single process, increasing the production capacity and the tool is easy to movearound. The results of the pantiaw cutter test resulted in uniform pieces of pantiaw in one press / process. Capacity 0.5 kg pantiaw processing with 30 seconds.